2012
DOI: 10.12811/kshsm.2012.6.3.029
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Depressive Symptom and Suicidal Thinking between the Elderly Living Alone and the Elderly Couples

Abstract: The aim of this study was to examine the spouse effects on depressive symptom and suicidal thinking among the elderly aged 65 and over in Korea. The subjects selected from the database of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 4 publications
3
5
1
2
Order By: Relevance
“…We found no statistically significant interaction term, suggesting that the relationship between living arrangements and suicidal thoughts are similar across attitudes toward marriage. Our finding that living arrangements are not significantly related to suicidal ideation is in contrast to previous research pertaining to the older population, in which living alone has been found to be related to decreased wellbeing and increased suicidal ideation (Fukuchi et al 2013;Han, Kang, and Jeong 2012;Masocco et al 2008). Additionally, our findings do not support the current social discourse on the negative psychological implications of living alone in young adulthood (Nho 2014).…”
Section: Suicidal Ideationcontrasting
confidence: 99%
“…We found no statistically significant interaction term, suggesting that the relationship between living arrangements and suicidal thoughts are similar across attitudes toward marriage. Our finding that living arrangements are not significantly related to suicidal ideation is in contrast to previous research pertaining to the older population, in which living alone has been found to be related to decreased wellbeing and increased suicidal ideation (Fukuchi et al 2013;Han, Kang, and Jeong 2012;Masocco et al 2008). Additionally, our findings do not support the current social discourse on the negative psychological implications of living alone in young adulthood (Nho 2014).…”
Section: Suicidal Ideationcontrasting
confidence: 99%
“…Sleeping time was significantly lower in one-person households than in multi-person households, which is consistent with the finding of Han et al 14) that elderly people living alone sleep 6.05 hours a day, less than 6.59 hours a day for couple elderly. This is because most of the elderly people living alone lack the economic and social support…”
Section: Logistic Analysis To Compare Health and Medical Characteristsupporting
confidence: 91%
“…Although there are many studies focusing on socio-demographic factors, 3) nutritional behavior, 8,9) quality of life, 5,10) and satisfaction, 6) there are only few studies focusing on health factors. Such studies only conducted short analysis for general health status, 1,11,12) mental health, [13][14][15][16][17][18] and oral health status.…”
Section: Introductionmentioning
confidence: 99%
“…노인 자살생각에 대한 선행연구를 살펴보면, 자살생각에 영향을 미치는 요 인으로 건강관련 요인 (Lee HK et al, 2012;Oh CS. 2012;Seomun JH et al, 2011)과, 심리사회적 요인 (Ha JM et al, 2012;Kong HS et al, 2012;Kim KT et al, 2011;Kim MY, 2010)에서 영향요인을 찾았고, 독거노인 관련 자살생각 (Han SS et al, 2012;Ko JU et al, 2011;Yang OK et al, 2011;Song YD et al, 2010), 노인성별에 따른 자살생각 (Koo CY et al, 2014) 등으로, 가구형태 및 성별에 따라 노인의 자살생 각에 대한 다양한 연구가 이루어져 왔다.…”
unclassified
“…특히 우울은 자살생각을 예측하는 가장 강력한 영향요인으로 나타났다 (Koo CY et al, 2014;Sohn SY, 2014;Kang WS et al, 2013;Seomun JH et al, 2011;Kim KT et al, 2011;Song YD et al, 2010;Kim HK et al, 2010;Kim MY, 2010;Park BG, 2008) (Kim HS et al, 2007), 건강상태가 나 쁠수록 자살생각의 빈도나 자살생각 정도가 높은 것으로 나타난 반면 (Sohn SY, 2014;Kwon OG et al, 2013;Ha JM et al, 2012;Kim KT et al,2011;Kim MY, 2010;Han SS et al, 2009) Kim HK et al, 2010;Han SS et al, 2009;Kim SH et al, 2007). 또한 유배우자 노인이 무배우자 노인보다 자살생각 을 약 40% 적게 하였으며 (Han SS et al, 2012), 부부 노인에 비해 독거노인이 자살생각을 2.2배 더 많이 경험하는 것으 로 나타났다 (Han SS et al, 2009) (Sohn SY, 2014;Kang WS et al, 2013;Ha JM et al, 2012;Yang NY et al, 2012;Oh CS, 2012;Park JS et al, 2009) (Koo CY et al, 2014;Sohn SY, 2014;Kang WS et al, 2013;Seomun JH et al, 2011;Kim KT et al, 2011;Song YD et al, 2010: Kim SH et al, 2007. …”
unclassified